2013
DOI: 10.1111/evj.12085
|View full text |Cite
|
Sign up to set email alerts
|

A long‐term study on the clinical effects of mechanical widening of cheek teeth diastemata for treatment of periodontitis in 202 horses (2008–2011)

Abstract: SummaryReason for performing study: Cheek teeth diastemata are a common cause of painful periodontal disease in horses, but there is limited objective information on their treatment. Objective: To assess the long-term response to diastema widening in clinically affected horses. Study design: Retrospective study. Method: Medical records from cases of cheek teeth diastemata treated by diastema widening referred to the University of Edinburgh Equine Hospital from 2008 to 2011 were analysed. Results: During this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 16 publications
2
28
1
1
Order By: Relevance
“…The significantly higher prevalence of diastemata in the older age groups is attributed more to the development of senile diastemata, as described in horses. They develop after continued eruption of teeth and a decreasing crown diameter toward the apices, resulting in decreased surface area at the level of the occlusal surface 33 . The strong association between the prevalence of diastemata and PD also has been noted in other species 19,20,30 .…”
Section: Discussionmentioning
confidence: 87%
“…The significantly higher prevalence of diastemata in the older age groups is attributed more to the development of senile diastemata, as described in horses. They develop after continued eruption of teeth and a decreasing crown diameter toward the apices, resulting in decreased surface area at the level of the occlusal surface 33 . The strong association between the prevalence of diastemata and PD also has been noted in other species 19,20,30 .…”
Section: Discussionmentioning
confidence: 87%
“…In a university referral practice, mandibular 09–10 diastemata comprised 24.8% of all cases treated by diastema widening (Dixon et al . ). In studies where an oral endoscope was used to examine the oral cavity, clinicians found diastemata at all interproximal sites with the lower and upper 06–07s and 10–11s most commonly affected (Simhofer et al .…”
Section: Prevalence and Locationmentioning
confidence: 97%
“…As the distal pulp horns of cheek teeth lie very close to the caudal aspect of the teeth, an attempt must be made to remove most of the dental tissue from the rostral aspect of the tooth lying caudal to the diastema (Bettiol and Dixon ; Dixon et al . ). Following this procedure, many horses experiencing severe oral pain and quidding become asymptomatic within a week or so of treatment and some younger horses are permanently cured (Dixon ; Rucker ; Dixon et al .…”
Section: Treatmentmentioning
confidence: 97%
“…The 6 cheek teeth (CT) of the horse should act as a single grinding unit with tight interproximal contact due to the opposing angulation of the 06 s, 10 s and 11 s. Diastemata (inappropriate gaps between the CT) and associated periodontal disease is recognised as the main cause of oral pain and quidding in referral cases (Collins and Dixon ; Dixon et al . , ). Diastemata can be divided into ‘valve‐type’ or ‘open‐type’ and most frequently involve the caudal 2 mandibular interdental spaces – making diagnosis and treatment a challenge (Collins and Dixon ).…”
Section: Introductionmentioning
confidence: 99%
“…For valve type diastemata – widening with a mechanised burr has been shown to be an effective treatment for carefully selected cases (Dixon et al . , ).…”
Section: Introductionmentioning
confidence: 99%